(3aJM GdhUjO aj TQM GdbUjOs - (3Yde GdOjf CHh GdMSf Ydj Hf eMeO Hf YHO GdUeO GdSNGhis; (3GdTGWHj GdebQF GdVQjQ , CHh eMeO,J (B590 (3g` s ((3CMeO Hf YKeGf Hf GdLfRi s)
(3ChdgG (B:s
(3HSe Gddg ai GdfXe GhdkG JHGQc QMeGfkG QjMekG hehFdG bhdg HSe Gddg RGO aCONd Ydi GdHGA HGA MQUkG Ydi GdGeJfGf s
(3BNQgG (B:s
(3heG NGH Ph LO EPG gh MHdGA Ydi TQWi Ci Ydi eG TQWJg ef GdQehR heG bOeJg ef GdbjhO hMSHc EPG bGd MSHi Gddg BNQ Gd LRA GdChd ef aJM GdhUjO ai TQM GdbUjO hGdMeO ddg hMOg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs